Infestation with the cat flea, ctenocephalides felis felis (siphonaptera pulicidae) among students in Kuala Lumpur, Malaysia - Chin, H.C.; Ahmad, N.W.; Lim, L.H.; Jeffery, J.; Hadi, A.A.; Othman, H.; Omar, B. (SEAMEO Regional Tropical Medicine and Public Health Network, 2010)
This paper reports six male undergraduate students living at a local university hostel who were infested with cat fleas (Siphonaptera Pulicidae Ctenocephalides felis felis) m February 2009 All of them suffered from maculopapular rashes and severe pruritus after the bites Investigation revealed the presence of a stray cat in the hostel building, five of the students had a history of contact with the cat Six cat fleas were collected at the hostel and identified as C felis felis Most of the students were not aware of this infestation and did not seek medical treatment